Current knowledge and future perspectives of bone replacement grafts - KASSIR, Abdel Rahman; CHAKAR, Carole (International Arab Journal of Dentistry (IAJD), 2020)
Bone and periodontal regenerative procedures represent a fundamental component of periodontal practice. While autologous bone graft has always been considered the ideal material for the repair and/or reconstruction of craniofacial defects, its limited availability and harvesting-associated complications and discomfort lead to a substantial interest in bone replacement grafts (BRG) throughout the years. With increasing technological advances and understanding, the spectrum of BRG has broadened and taking into consideration that not all BRM perform in the same way, the appropriate clinical choice needs to be performed among the large varieties of available biomaterials. Because an understanding of the properties of each BRG enables individualized clinical selection, the objective of this article is to provide a review on the different types of BRG intended for reconstructive therapy and provide an overview on the current innovations and future perspectives in this field.